Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), dan Dana Bagi Hasil (DBH) Terhadap Belanja Modal Pemerintah Kabupaten/Kota di Provinsi Bengkulu Tahun 2019-2023 - Putri, Meizah Dwi; L.V, Yuhendri (Jurnal Ecogen, 2025)
This study aimed at analyzing the influence of Economic Growth, Local Own-Source Revenue (PAD), General Allocation Fund (DAU), and Profit-Sharing Fund (DBH) on Capital Expenditures in the District/City Bengkulu Province Year 2019-2023. The study population is the 10 districh/cities that make up the Regency/City of Bengkulu Province 2019-2023. Realization reports and other secondary date are used in this research sourced from DJPK and BPS statistics using the documentation method. This research approach uses a quantitative approach with an associative research type and data analysis technique using panel data regression with Eviews12. The result of the research show that (1) Economic Growth have positive and significant influence to Capital Expenditure, (2) Local revenue (PAD) have significant positive impact on Capital Expenditure, (3) General Allocation Funds (DAU) do not affect Capital Expenditure, (4) Revenue-Sharing Funds (DBH) do not affect Capital Expenditure, (5) The result of the research show that Economic Growth, PAD, DAU and DBH have significant influence to Capital Expenditure of the Regencies and Cities in Bengkulu Province the 2019-2023.